Platelet-Derived Extracellular Vesicles as Target of Antiplatelet Agents. What Is the Evidence? - Taus, Francesco; Meneguzzi, Alessandra; Castelli, Marco; Minuz, Pietro (Frontiers in Pharmacology, 2019)
Platelet-derived large extracellular vesicles (often referred to as microparticles in the field of cardiovascular disease) have been identified as effector in the atherothrombotic process, therefore representing a target of pharmacological intervention of potential interest. Despite that, limited evidence is so far available concerning the effects of antiplatelet agents on the release of platelet-derived extracellular vesicles. In the present narrative review, the mechanisms leading to vesiculation in platelets and the pathophysiological processes implicated will be discussed. This will be followed by a summary of the present evidence concerning the effects of antiplatelet agents under experimental conditions and in clinical settings.